Islamic-Based Management of Early Childhood Anxiety for Character and Cognitive Development - M, Alyka Shalsabilah; Mutmainnah; Martuty, Arie; Rahmat, M. Yusran (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
Early childhood anxiety, as a form of mild mental disorder, can hinder cognitive development if not identified and managed appropriately. This study aims to explore the characteristics and causal factors of anxiety in children aged 5–6 years, as well as to examine teacher–parent collaboration in managing anxiety within the framework of Islamic early childhood education. This research employed a qualitative case study approach involving children, teachers, and parents at a kindergarten setting. Data were collected through participant observation, in-depth interviews, and documentation during September 2025. The findings reveal that children exhibited symptoms such as excessive fear, social withdrawal, and decreased concentration, which negatively affected their learning processes. Contributing factors included inconsistent parenting, academic pressure, limited teacher competence in early detection, and weak coordination between school and home. From an Islamic educational perspective, managing anxiety is part of tarbiyah that nurtures children’s emotional balance, faith, and character (akhlaq). Teacher–parent collaboration reflects the principle of amanah (educational responsibility), fostering a supportive environment characterized by compassion, patience, and empathy. Practical strategies such as consistent communication, play-based learning, storytelling, and emotional support contribute to children’s psychological security and readiness to learn. This study highlights that integrating emotional care with Islamic values supports holistic child development, combining cognitive growth with spiritual and moral formation in early childhood education.